Hubungan antara Kejadian Bayi Berat Lahir Rendah dengan Konsumsi Protein Hewani di RSU Karsa Husada - Ririn Triwidiasti; Feriana Ira Hardian; Risna Yekti Mumpuni (Jurnal Akademika Baiturrahim Jambi, 2023)
Pregnant women really need good nutrition, especially consumption of animal protein for fetal growth so as not to experience obstacles and give birth to babies with normal birth weight. perinatology of Karsa Husada General Hospital. The sample in this study was taken using puposive sampling as many as 40 repondentsres. Correlation test using Pearson's product moment. This study showed that most (67.5%) mothers consumed animal protein in the low category during pregnancy and (52.5%) the babies were born with a baby weight of <2500 g. The results of the analysis using the Spearman rank test showed that the value of p = 0.01 or p < 0.05 and the value of r = -.623 showed a strong correlation and had a negative direction, meaning that the higher consumption of animal protein in the mother, the incidence of LBW will be lower. From the results of the study, it can be recommended for pregnant women to consume good nutrition, especially consumption of animal protein during pregnancy for fetal growth and give birth to babies with normal birth weight